The three-dimensional kinematics of a barbell during the snatch of Taiwanese weightlifters - Chiu, H.-T.; Wang, C.-H.; Cheng, K. B. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study is to characterize the trajectory of a barbell and clarify whether there is a standard pattern in the barbell trajectory for each lifter. Two high-speed cameras (mega-speed MS1000, sampling rate = 120 Hz) were used to film the barbell trajectories of male Taiwanese weightlifters under competitive conditions. Twenty-four successful lifts were filmed and classified into 3 groups (n = 8 per group) by relative barbell-mass (RBM): the better-performance group (RBM > 1.63), the middle group (1.28 < RBM < 1.63), and the worse-performance group (RBM < 1.28). The results indicate that 3 horizontal (the horizontal position of the barbell at clearing the knee of the lifter, projectile range, and the horizontal velocity of the barbell at its highest position) and 3 vertical variables (the barbell's maximum vertical height, the maximum height normalized by the height of the catch position, and the vertical displacement from the maximum height to the catch position) of the barbell movements in the sagittal plane were significantly different in the 3 groups (p < 0.05). A greater vertical travel range of the barbell (19.5 ± 1.9 cm) was found for the better-performance group than for the results of male weightlifters (about 10-14 cm) in previous studies. Although the barbell movement patterns in the vertical direction were similar, there seemed to be no standard trajectory for each weightlifter because of the variation in horizontal movements. The results of this study suggest that weightlifters may be instructed to reduce horizontal velocity and increase the vertical travel range of the bar to catch it under the conditions of less strength (as in female lifters) or heavier barbell mass.